2023
DOI: 10.3389/fmicb.2023.1071603
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of demethylated hydroxylated phillygenin derivative on Helicobacter pylori infection

Abstract: Modifying and transforming natural antibacterial products is a novel idea for developing new efficacious compounds. Phillygenin has an inhibitory effect on H. pylori. The aim of the present study was to prepare a phillygenin derivative (PHI-Der) through demethylation and hydroxylation. The minimum inhibitory concentration of 18 strains of H. pylori from different sources was 8–32 μg/mL in vitro, and the activity increased 2–8 times than that of phillygenin. PHI-Der could significantly inhibit the colonization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The pharmacokinetics of phillygenin in rats exhibit first-order kinetics, with rapid distribution and elimination, while in mice, also shows high oral bioavailability, peaking within 30 min [ 11 , 12 ]. Previous studies have shown that phillygenin has diverse biological activities, including anti-inflammatory, antioxidant, antitumor, antibacterial, antiviral, analgesic, and hepatoprotective effects [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Since free radical-induced oxidative damage to the brain is recognized as a primary cause of neuronal death in various neurodegenerative disorders, compounds with antioxidative properties, such as phillygenin, may be effective at preventing or delaying these central nervous system (CNS) disorders [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacokinetics of phillygenin in rats exhibit first-order kinetics, with rapid distribution and elimination, while in mice, also shows high oral bioavailability, peaking within 30 min [ 11 , 12 ]. Previous studies have shown that phillygenin has diverse biological activities, including anti-inflammatory, antioxidant, antitumor, antibacterial, antiviral, analgesic, and hepatoprotective effects [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Since free radical-induced oxidative damage to the brain is recognized as a primary cause of neuronal death in various neurodegenerative disorders, compounds with antioxidative properties, such as phillygenin, may be effective at preventing or delaying these central nervous system (CNS) disorders [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori infection involves the colonization of the stomach by the of antibiotic-resistant strains of H. pylori, which can make treatment more difficult. In addition, long-term use of PPIs has been associated with adverse effects, including increased risk of infection, kidney disease, and bone fractures [4]. Studies have shed light on the pathogenesis of H. pylori infection, including the role of virulence factors such as CagA and VacA, and the interaction between H. pylori and the host immune system [5].…”
Section: Introductionmentioning
confidence: 99%